Estudo in vitro do efeito da interferência por RNA (RNAi) na replicação do vírus da hepatite C - Carneiro, Bruno Moreira [UNESP] (2013)
Hepatitis C virus (HCV) frequently establishes persistent infections in the liver, leading to the development of chronic hepatitis, and, potentially, to liver cirrhosis and hepatocellular carcinoma at later stages. No vaccine is available for HCV and the current standard of care, which consists of pegylated interferon-? and ribavirin, has limited efficacy against certain HCV genotypes, and also produces significant adverse effects. Molecular therapies have proven to be effective in the inhibition of the virus in vitro. Molecular therapies based on RNAi has shown good efficiency on knockdown of HCV in vitro.The aim of this study was to develop different methodologies for inhibiting HCV replication using the RNAi technique. We developed five dicer substrate siRNA molecules, which mostly were able to reduce viral replication by 90% compared to the negative control. Still, there was no selection of resistant mutants of the virus after treatment with DsiRNAs for 21 days. In addition, we developed lentiviral vectors containing sequences encoding shRNA against HCV. With the use of these lentiviral particles, it was possible to reduce HCV replication by approximately 99% compared to negative control. In this study, it was demonstrated that HCV could be effectively inhibited using different RNAi technologies. The DsiRNAs are more powerful than traditional siRNAs and less likely to select resistant mutants. The lentiviral vectors are efficient in delivery of genes containing shRNAs and potent in the inhibition of HCV. Both technologies in the future may be used in alternative therapy for chronic patients or in case of DsiRNAs preventively to infection